Kajian Potensi Pemanfatan Limbah Tailing PT. Freeport Sebagai Bahan Stabilisasi Tanah Untuk Perkerasan Jalan - irianto; Didik S. S. Mabui; R. Rochmawati; Ardi. A. Sila; A. Yunianta; A. Rasyid (BAKTI : Jurnal Pengabdian Kepada Masyarakat, 2021)
Problems that often occur in road infrastructure, especially in the Papua region, are wavy, cracked and subsidence of the land. Damage to buildings in the form of cracks in walls and floors and building subsidence is sometimes caused by poor physicalzand mechanicalzcharacteristicszof thezsoil. Soil stabilization on the subgrade of a construction is a method used to improve the properties of the subgrade. Tailing waste utilization of PT. Freeport will greatly assist the government's program in overcoming environmental pollution as well as as a soil stabilization material for road construction. The purposezof thiszstudyzwas tozdetermine whetherzthe land in the Musamus University, Merauke area is suitable for stabilization using tailing PT. Freeport and to determine the optimum value of tailings used as a stabilizing agent to reduce the value of the original soil Plasticity Index. The original soil plasticity index value is 28.96%, the soil plasticity index value at 5% tailings content is 17.2395%, at 10% tailings grade is 10.1402%, at 15% tailings grade is 5.4228%, at 10% tailings grade. 20% tailings by 6.8704%. So that the soil is suitable to be stabilized using tailings and the optimum level of tailings used is at a level of 15%.